Hair cortisol and work stress: Importance of workload and stress model (JDCS or ERI). (March 2018) - van der Meij, Leander; Gubbels, Nikkie; Schaveling, Jaap; Almela, Mercedes; van Vugt, Mark
Highlights: Hair cortisol and self-reported stress: literature shows mixed findings. Many studies do not use stressed samples or distinguish between sources of stress. This study: self-reported stress related to hair cortisol only in high workload sample. Effort reward imbalance with high overcommitment was related to higher hair cortisol. A stress threshold may need to be reached to produce changes in hair cortisol. Abstract: Hair cortisol concentrations (HCCs) are a potential physiological indicator of work related stress. However, studies that tested the relationship between HCC and self-reported stress in a work setting show mixed findings. This may be because few studies used worker samples that experience prolonged stress. Therefore, we compared a high workload sample ( n  = 81) and a normal workload sample ( n  = 91) and studied whether HCC was related to: (i) high job demands, low control, and low social support (JDCS model), and (ii) high effort, low reward, and high overcommitment (ERI model). Results showed that self-reported stress related to HCC only in the high workload sample and only for the variables of the ERI model. We found that HCC was higher when effort was high, reward low, and overcommitment high. An implication of this study is that a certain stress threshold may need to be reached to detect a relationship between self-reported stress and physiological measures such as HCC.